MORAL EDUCATION IN ISLAM AS AN EFFORTS TO PREVENT LGBT BEHAVIOR AMONG TEENAGERS - Muhammad Nasri Sitorus; Hasnil Aida (Jurnal Bilqolam Pendidikan Islam, 2026)
The phenomenon of LGBT behavior among adolescents has become a serious concern in education and society because it is considered to influence the moral, social, and spiritual development of the younger generation. This study aims to analyze the role of Islamic moral education as an effort to prevent LGBT behavior among adolescents. This research uses a qualitative method with a library research approach by collecting and analyzing various literature sources such as the Qur'an, hadiths, books, scientific journals, and academic works related to moral education and LGBT behavior. The results show that moral education in Islam plays an important role in shaping adolescent character through the cultivation of faith values, self-control, modesty, responsibility, and habituation of behavior in accordance with Islamic teachings. Moral education implemented from an early age through family, school, and community environments can serve as a moral fortress for adolescents in facing the negative influences of modern developments. Therefore, Islamic moral education is considered one of the preventive solutions in maintaining adolescent behavior and moral identity in accordance with Islamic values.